Grundtvigs natursyn - Pedersen, Kim Arne (Grundtvig-studier, 1989)
Grundtvig’s conception of Nature.By Kim Arne Pedersen.In this paper Grundtvig’s view on non-human nature and natural science is examined with the contemporary Danish discussion about theology and natural sciences (Viggo Mortensen) as a starting-point. It is argued against the use of Grundtvig’s ideas as a model for a dialogue between these fields of scholarship.Earlier researchers’ (C. I. Scharling) denial of Grundtvig having a view on nature is rejected, and Kaj Thaning’s conception of the autonomy of natural sciences in Nordens Mythologi 1832 is modified.Grundtvig’s conception of nature is defined as rooted in the Western European theological tradition’s Neo-platonic oriented cosmological interpretation of Genesis. Grundtvig takes up the understanding of natural objects as images of the invisible, spiritual world, but he shows his awareness of the rational, scientific interpretation of this tradition.The article points out 4 phases in Grundtvig’s elaboration of his view on nature after 1810, connected with the years after Kort Begreb af Verdens Krønike 1812, the magazine Danne-Virke 1816-1819, the years after Nordens Mythologi 1832 and the period from 1855 to 1860-1865. In the first phase Grundtvig rejects the independence of natural sciences as a tool of Antichrist in the final battle of the near future. In Danne-Virke nature is understood as a tool used in man’s symbolic knowledge of God. The main tool is man’s knowledge of himself because of his exceptional position inside creation as a creature with self-consciousness and language, and therefore the natural sciences are subordinated research on the history of man. Grundtvig’s thesis of femininity as representing nature and man’s body as a microcosm both in a rational, scientific and in a symbolic way is connected with this leading idea. In the years after Nordens Mythologi Grundtvig gives nature and natural sciences a much more independent position, but at the same time he stresses nature’s connection with man because of the state of man’s body as a microcosm. Grundtvig also attacks the Copernican picture of the universe.In the years after 1855 Grundtvig’s attitude towards natural science is sharpened. Apocalyptic motives return, and now Antichrist is connected with the rejection of God’s omnipotence and man’s exceptional position inside creation. As an alternative to the natural sciences Grundtvig emphasizes the interpretation of nature as a symbolic image of God.